Green consumerism, green perceived value, and restaurant revisit intention: Millennials' sustainable consumption with moderating effect of green perceived quality. (17th March 2022) - Riva, Farzana; Magrizos, Solon; Rubel, Mohammad Rabiul Basher; Rizomyliotis, Ioannis
Abstract: Adopting green practices does not always guarantee customer retention and loyalty. Employing the theoretical lens of cue utilization theory, we conceptualize green perceived quality as sending internal and external cues which help consumers form judgments about product quality and perceived value. Based on a survey of 280 restaurant customers, we hypothesize and report a positive and significant influence of both green consumerism and green perceived value on customer revisit intention. Further, the results confirm the moderating role of green perceived quality. From a practical point of view, managers interested in benefiting from the green practices of their restaurants should focus on increasing their customers' evaluation and overall judgment of the environmental quality of both their food and services.